2015
DOI: 10.1177/0284185114551565
|View full text |Cite
|
Sign up to set email alerts
|

Automated breast ultrasound system (ABUS): reproducibility of mass localization, size measurement, and characterization on serial examinations

Abstract: The ABUS provided reproducible images for mass localization, size measurement, and characterization, which may be useful for follow-up studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 26 publications
1
24
1
2
Order By: Relevance
“…ABVS has emerged as a digital and automatic3D US technology withtheadvantages of less operatordependence and high reproducibility [14].It can reconstruct entire breast images from coronal and sagittal views, allowing multiplanar display and true US tomography of the breast [13]. A meta-analysis showed high sensitivity and specificity of ABVS in differentiating benign and malignant breast lesions (92% and 84.9%, respectively) [24], and other studies demonstrated equivalent diagnostic accuracy of ABVS compared with conventional US [8,9,10,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABVS has emerged as a digital and automatic3D US technology withtheadvantages of less operatordependence and high reproducibility [14].It can reconstruct entire breast images from coronal and sagittal views, allowing multiplanar display and true US tomography of the breast [13]. A meta-analysis showed high sensitivity and specificity of ABVS in differentiating benign and malignant breast lesions (92% and 84.9%, respectively) [24], and other studies demonstrated equivalent diagnostic accuracy of ABVS compared with conventional US [8,9,10,25].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the similar usefulness of BI-RADS-US descriptors in diagnosing breast lesions, it is significant to know how retraction phenomenon performed compared with BI-RADS-US descriptors in the differential diagnoses of breast lesions. Although the literature concerning the clinical application of ABVS has been currently increasing, studies have mainly focused on thediagnostic value of ABVS [11,12,13], its reproducibility [14,15,16], itscomparison with conventional US or mammography [8,9,10,17], disease size measurement [18,19], and its application to other organs or tissues [20,21]. To our knowledge, no investigators have compared the diagnostic performance of retraction phenomenon with BI-RADS-US descriptors using an ABVS.…”
mentioning
confidence: 99%
“…Handheld ultrasound (HHUS) is a standard imaging modality of the breast; however, HHUS has several drawbacks, such as a long examination time and low rate of reproducibility [3][4][5]. Automated breast ultrasound (ABUS) can overcome the shortcomings of HHUS [6][7][8] while maintaining diagnostic performance [9][10][11][12]. Furthermore, ABUS provides a wide field of view and coronal sections of the breast, which has the advantage of showing spiculated margins of breast cancer and architectural distortion [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the generated coronal plane may offer new diagnostic information (4). It was proposed that ABUS may be used to monitor breast cancer patients treated with NAC (5). …”
Section: Introductionmentioning
confidence: 99%